Development of Green Method for Trace Determination of Bendiocarb in Real Samples Using Emerson - Baghdad Science Journal (مجلة بغداد للعلوم)
In this study, cloud point extraction combined with molecular spectrometry as an eco-friendly method is used for extraction, enrichment and determination of bendiocarb (BC) insecticide in different complex matrices. The method involved an alkaline hydrolysis of BC followed Emerson reaction in which the resultant phenol is reacted with 4-aminoantipyrene(4-AAP) in the presence of an alkaline oxidant of potassium ferric cyanide to form red colored product which then extracted into micelles of Triton X-114 as a mediated extractant at room temperature. The extracted product in cloud point layer is separated from the aqueous layer by centrifugation for 20 min and dissolved in a minimum amount of a mixture ethanol: water (1:1) followed the determination of BC by using spectrophotometry at a wavelength maximum of 470 nm. The most important parameters affecting the extraction and determination of BC are conducted via a classical optimization. Under the optimum conditions established , Beer’s law is obeyed in the range of 0.1-4 µg mL-1 while the optimum concentration ranges estimated by Ringbom’s plot was of 0.4-2.12 µg mL-1. The enrichment factor was of 59.87 fold leading to achieve the limit of detection of 0.076 ?g mL-1. The proposed method gives superior sensitivity in terms of the molar absorptivity of 1.99x105 L mol-1 cm-1 and extraction efficiency of 98.0%. The established method is applied in the analysis of the spiked vegetables, orange, soil and water samples with appropriate concentration with BC standard.